Geodiversity of Ciletuh-Palabuhanratu UNESCO Global Geopark, Sukabumi, West Java - Nugraha Ardiansyah; Katon Sena Aji Nugraha; Rinaldi Ikhram (Ikatan Ahli Geologi Indonesia, 2019)
Ciletuh-Palabuhanratu UNESCO Global Geopark (CPUGG) is located in the southwest of Sukabumi Regency, West Java, Indonesia. It covers an area of 126,000 ha or 1260 km2. CPUGG has several rare geodiversity features that can be classified into the theme: “The subduction zone uplifted, Ancient magmatic zone shifting and fore arc evolution”. This paper presents a summary of geodiversity features within CPUGG, Data sources are to be found on CPUGG’s website and in the scientific publications in the references. Within CPUGG 24 geosites contain one or more objects. All are of local, national, and international value. In addition, each geosite has also applications in scientific research, educational and touristic value or both. The geosites are: Cisolok Geyser (the only geyser in Indonesia), the Mega Amphitheatre (the Biggest Natural Amphitheatre in Indonesia), the Pasir Luhur Complex (Metamorphic Rocks) and the Gunung Beas Complex (Ophiolites). Some heritage sites contain rare rocks and fossils such as Ciletuh Formation (Batu Naga, Karang Daeu, etc.) the oldest sedimentary deposits in West Java.